2010
DOI: 10.1186/1423-0127-17-12
|View full text |Cite
|
Sign up to set email alerts
|

Shorter GT repeat polymorphism in the heme oxygenase-1 gene promoter has protective effect on ischemic stroke in dyslipidemia patients

Abstract: BackgroundThe microsatellite polymorphism of heme oxygenase (HO)-1 gene promoter has been shown to be associated with the susceptibility to ischemic event, including coronary artery disease (CAD), myocardial infarction, and peripheral vascular disease. We aimed to examine whether the length of (GT)n repeats in HO-1 gene promoter is associated with ischemic stroke in people with CAD risk factors, especially low level of HDL.MethodsA total of 183 consecutive firstever ischemic stroke inpatients and 164 non-strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Of these, three large studies 1517 , including 1800 to 3000 patients, found no relationship between HO-1 VNTR repeat length and their primary endpoints restenosis 15,17 or coronary artery disease 16 , but a large number of smaller studies did.Putting these data in perspective with our study, it should be considered that HO-1 induction occurs in response to stress conditions 10,11,18 , and a more severe deficit in HO-1 might be necessary in the general (low-risk) population to evoke deleterious effects, whereas a less severe deficit could suffice in higher-risk patients. This interpretation is consistent with several reports that found an association between HO-1 VNTR length and vascular endpoints only in high-risk sub groups such as diabetic subjects or smokers 11,13,19,20 .…”
Section: Discussionsupporting
confidence: 93%
“…Of these, three large studies 1517 , including 1800 to 3000 patients, found no relationship between HO-1 VNTR repeat length and their primary endpoints restenosis 15,17 or coronary artery disease 16 , but a large number of smaller studies did.Putting these data in perspective with our study, it should be considered that HO-1 induction occurs in response to stress conditions 10,11,18 , and a more severe deficit in HO-1 might be necessary in the general (low-risk) population to evoke deleterious effects, whereas a less severe deficit could suffice in higher-risk patients. This interpretation is consistent with several reports that found an association between HO-1 VNTR length and vascular endpoints only in high-risk sub groups such as diabetic subjects or smokers 11,13,19,20 .…”
Section: Discussionsupporting
confidence: 93%
“…In two previous studies conducted in Japan (279 controls and 298 CHD patients) (Kaneda et al 2002) and Taiwan (322 controls and 664 CHD patients) ), significant associations were found between HO-1 gene promoter polymorphism and CHD risk in subjects with one of the CHD risk factors; another study (Bai et al 2010) also found that (GT) n repeats in HO-1 gene promoter may affect cerebral ischemic risk in dyslipidemia patients. Our study is broadly consistent with these results, however, we further demonstrated for the first time that this association may be attributed to the interaction between HO-1 gene promoter and OS.…”
Section: Discussionmentioning
confidence: 89%
“…Among arsenic-exposed individuals in Taiwan, the carriers of the short (GT) n polymorphisms in the HO-1 gene promoter had lower rates of CV mortality and hypertension and a lower probability of developing carotid atherosclerosis (11,27,28). With regard to ischemic cerebrovascular events, one study reported that patients with long (.26 GT) repeats in the HO-1 gene promoter had greater susceptibility for developing ischemic stroke in the presence of low HDL cholesterol (29). Our finding corroborates the concept that the polymorphism of HO-1 is associated with CVD risk in the high-risk population; patients with CKD, especially ESRD on chronic HD, are definitely a highrisk population for CVD.…”
Section: Discussionmentioning
confidence: 99%